EFEKTIVITAS PENGGUNAAN APLIKASI MOBILE FITCLASS TERHADAP AKTIVITAS FISIK DAN MOTIVASI BELAJAR DALAM PENDIDIKAN JASMANI - Butsiarah; Alim, Bahrul (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2025)
This study aims to examine the effectiveness of the FitClass mobile application in improving physical activity and learning motivation among senior high school students in Physical Education. The study is motivated by the low levels of student participation in conventional PE learning and the need for technology-based innovations to enhance engagement and outcomes. A quasi-experimental method was employed using a pretest-posttest design involving both experimental and control groups. The research involved 60 Grade XI students from a senior high school, randomly assigned into two groups. The experimental group used the FitClass mobile application over a six-week period, while the control group followed conventional learning methods. Data were collected using physical activity observation sheets and a learning motivation questionnaire. The results indicated a significant increase in both physical activity (p < 0.05) and learning motivation (p < 0.05) in the experimental group compared to the control group. These findings suggest that the FitClassmobile application is effective in enhancing physical activity and learning motivation in high school Physical Education.